Dream West : politics and religion in cowboy movies - Brode, Douglas, 1943- (Austin : University of Texas Press, 2013)
"Overturns conventional thinking that the Western genre is essentially conservative. Instead, Brode demonstrates that Hollywood liberals used Westerns to espouse a progressive agenda on a range of issues, including gun control, environmental protection, respect for non-Christian belief systems, and community cohesion versus rugged individualism. Doug Brode takes a new look at dozens of Westerns, including Gunfight at the O.K. Corral, Red River, 3:10 to Yuma (old and new), The Wild Ones, High Noon, My Darling Clementine, The Alamo, and No Country for Old Men"--
part one. Cowboy politics: Roosevelt through Reagan -- part two. God's country: Religion in the western film.
Includes bibliographical references and indexes.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Western films -- History and criticism; Politics in motion pictures; Religion in motion pictures; Electronic books